Navigating the Selected SDGs: Unraveling Past Shortcomings for a Future of Prosperity - Waheed, Ayesha; Kiani, Muhammad Mohsin Latif (Pakistan Journal of Humanities and Social Sciences, 2024)
This study examines the United Nations' development framework, encompassing the Millennium Development Goals (MDGs) and Sustainable Development Goals (SDGs), in the context of Pakistan's engagement and advancement. While MDGs faced challenges in Pakistan due to diverse factors, SDGs were embraced as the nation's blueprint for development with a well-coordinated institutional setup. The study's main objective is to assess the institutional coordination and implementation of SDGs at national and provincial tiers. Through comprehensive stakeholder interviews and an analysis of specific SDG indicators, the study identifies regions with varying degrees of susceptibility to falling short of set targets. The research assessed annual progress levels and compared them to the 2030 targets, using data from PSLM and PDHS surveys. Districts were categorized based on their estimated annual change requirements, offering a concise overview of indicator status in Pakistan. The findings underscore the potential challenges faced by Sindh, Baluchistan, and specific districts in KP, shedding light on Pakistan's trajectory towards sustainable development.